Employee–Spouse Perceptual Congruence in Employee Work-to-Family Enrichment Affects Family and Work Outcomes: The Mediating Role of Relationship Conflict - Chen, Jianlan; Tian, Yu (Frontiers in Psychology, 2021)
Various studies have demonstrated that work-to-family enrichment is beneficial for employees in both the work and home domains. However, these findings may overstate the benefits of work-to-family enrichment and ignore its potential dark side. We advance the research on work-to-family enrichment by integrating conflict theory with concept of work-to-family enrichment to investigate whether and how employee-spouse perceptual congruence in employee work-to-family enrichment influences employee family cohesion and emotional exhaustion. The results of polynomial regressions on 225 employee and spouse dyads revealed that the perceptual congruence in employee work-to-family enrichment between employees and spouses was negatively associated with relationship conflict. Additionally, asymmetrical incongruence effects were found, wherein spouses perceived higher relationship conflict with employees when their perceptions of employee work-to-family enrichment were lower than those of the employees. Furthermore, spouses’ perceived relationship conflict with employees mediated the influences of employee-spouse perceptual congruence in employee work-to-family enrichment on employee family cohesion and emotional exhaustion.